Autophagy Drives Galectin-1 Secretion From Tumor-Associated Macrophages Facilitating Hepatocellular Carcinoma Progression - Davuluri, Goutham Venkata Naga; Chen, Chien-Chin; Chiu, Yen-Cheng; Tsai, Hung-Wen; Chiu, Hung-Chih; Chen, Yuh-Ling; Tsai, Pei-Jane; Kuo, Wan-Ting; Tsao, Nina; Lin, Yee-Shin; Chang, Chih-Peng (Frontiers in Cell and Developmental Biology, 2021)
Galectin-1 (Gal-1) is a secretory lectin with pro-tumor activities and is associated strongly with hepatocellular carcinoma (HCC) development. Although Gal-1 is a well-known soluble pro-tumor factor in the tumor microenvironment (TME), the secretion mode of Gal-1 is not clearly defined. On the other hand, in addition to cancer cells, Gal-1 is widely expressed in tumor stromal cells, including tumor-associated macrophages (TAMs). TAMs are a significant component of stromal cells in TME; however, their contributions in producing Gal-1 to TME are still not explored. Here we reveal that TAMs can actively secrete Gal-1 in response to stimuli of HCC cells. Gal-1 produced by TAMs leads to an increase of the systemic level of Gal-1 and HCC tumor growth in mice. Mechanistically, TLR2-dependent secretory autophagy is found to be responsible for Gal-1 secretion from TAMs. Gal-1 acts as a cargo of autophagosomes to fuse with multivesicular bodies via Rab11 and VAMP7-mediated vesicle trafficking before being secreted. This autophagy-regulated Gal-1 secretion in TAMs correlates to poor overall survival and progression-free survival rates of HCC patients. Our findings uncover the secretion mode of Gal-1 via secretory autophagy and highlight the pathological role of TAM-produced Gal-1 in HCC progression.